Education and Training in Pediatric Cardiac Critical Care. (November 2017) - McBride, Mary E.; Beke, Dorothy M.; Fortenberry, James D.; Imprescia, Annette; Callow, Louise; Justice, Lindsey; Bronicki, Ronald A.
Pediatric cardiac critical care is a new and emerging field. There is no standardization to the current education provided, and high-quality patient outcomes require such standardization. For physicians, this includes fellowship training, specific competencies, and a certification process. For advanced practice providers, a standardized curriculum as well as a certification process is needed. There is evidence that supports a finding that critical care nursing experience may have a positive impact on outcomes from pediatric cardiac surgery. A rigorous orientation and meaningful continuing education may augment that. For all disciplines and levels of expertise, simulation is a useful modality in the education in pediatric cardiac critical care.